Extended exome sequencing identifies BACH2 as a novel major risk locus for Addison's disease. (2nd November 2016) - Eriksson, D.; Bianchi, M.; Landegren, N.; Nordin, J.; Dalin, F.; Mathioudaki, A.; Eriksson, G. N.; Hultin‐Rosenberg, L.; Dahlqvist, J.; Zetterqvist, H.; Karlsson, Å.; Hallgren, Å.; et al.
Abstract: Background: Autoimmune disease is one of the leading causes of morbidity and mortality worldwide. In Addison's disease, the adrenal glands are targeted by destructive autoimmunity. Despite being the most common cause of primary adrenal failure, little is known about its aetiology. Methods: To understand the genetic background of Addison's disease, we utilized the extensively characterized patients of the Swedish Addison Registry. We developed an extended exome capture array comprising a selected set of 1853 genes and their potential regulatory elements, for the purpose of sequencing 479 patients with Addison's disease and 1394 controls. Results: We identified BACH2 (rs62408233‐A, OR = 2.01 (1.71–2.37), P = 1.66 × 10 −15, MAF 0.46/0.29 in cases/controls) as a novel gene associated with Addison's disease development. We also confirmed the previously known associations with the HLA complex. Conclusion: Whilst BACH2 has been previously reported to associate with organ‐specific autoimmune diseases co‐inherited with Addison's disease, we have identified BACH2 as a major risk locus in Addison's disease, independent of concomitant autoimmune diseases. Our results may enable future research towards preventive disease treatment.